The swimming holes of Texas - Wernersbach, Julie; Tracy, Carolyn (Jack and Doris Smothers series in Texas history, life, and culture ;, 2017)
"Nothing beats a natural swimming hole for cooling off on a scorching summer day in Texas. Cold, clear spring water, big old shade trees, and a quiet stretch of beach or lawn offer the perfect excuse to pack a cooler and head out with family and friends to the nearest natural oasis. Whether you're looking for a quick getaway or an unforgettable summer vacation, let The Swimming Holes of Texas be your guide. Julie Wernersbach and Carolyn Tracy highlight one hundred natural swimming spots across the entire state. The book is organized by geographic regions, so you can quickly find local places to swim?or plan a trip to a more distant spot you'd like to explore. Each swimming hole is illustrated with an inviting color photo and a description of what it's like to swim there, as well as the site's history, ecology, and conservation. The authors include all the pertinent info about admission fees and hours, parking, and on-site amenities such as showers and restrooms. They also offer tips for planning your trips and lists of the swimming holes that are most welcoming to families and pets"--Publisher's website